Design, Implementation, and Preliminary Evaluation of an Undergraduate Nursing Informatics Literacy Course Based on the ADDIE Model: A Single-Arm Mixed-Methods Study. - Zou, Huina; Wu, Linjing; Li, Kaixin; Chang, Polun; Chen, Yuan (Nursing Reports, 2026)
Background/Objectives: Nursing informatics competency is critical for nursing students entering clinical practice in the digital era. Current undergraduate nursing informatics courses prioritize theoretical instruction but lack sufficient integration with clinical applications, which restricts the depth of content delivery. This study aimed to design, implement, and conduct a preliminary evaluation of an undergraduate nursing informatics literacy course. Methods: This was a single-arm mixed-methods study. We implemented five sequential steps aligned with the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model: (1) needs assessment, (2) design of a systematic, progressive course spanning theoretical foundation, technical skills, and clinical application; (3) development of teaching materials and environment; (4) implementation through nine weekly 90 min sessions incorporating teach–practice–feedback; and (5) evaluation via a customized questionnaire and nursing informatics system project reports. Quantitative data were analyzed using the mean, standard deviation, and paired t tests; qualitative data were collected through post-course semi-structured interviews. Results: A total of 120 participants were enrolled from a provincial public medical school, of which 119 (99.2%) completed the course. Statistically significant pre–post improvements were observed in participants' nursing informatics competencies, informatics literacy self-efficacy, and innovative behavior after course completion (p < 0.001). Participants completed 12 group projects, which received two C grades, nine B grades, and one A grade. Overall course satisfaction averaged 89.03 ± 14.62. Qualitative interviews yielded three themes: (a) cognitive reconstruction and improvement in the ability to apply nursing informatics competencies, (b) dilemmas and breakthroughs in the integration of technology and knowledge in nursing informatics design, and (c) optimization direction of course content, design, and evaluation. Conclusions: An ADDIE-based nursing informatics literacy course may be associated with improvements in nursing informatics competencies, informatics literacy self-efficacy, and innovative behavior among nursing undergraduates. This study provides preliminary evidence supporting the feasibility and potential educational value of such a curriculum.